Antibody levels in a cohort of pregnant women after the 2009 influenza A(H1N1) pandemic: Waning and association with self‐reported severity and duration of illness. Issue 2 (1st January 2019) - Tunheim, Gro; Laake, Ida; Robertson, Anna Hayman; Waalen, Kristian; Hungnes, Olav; Næss, Lisbeth M.; Cox, Rebecca J.; Mjaaland, Siri; Trogstad, Lill
Abstract : Background: A population‐based pregnancy cohort was established in Norway to study potential effects of exposure to the 2009 influenza pandemic or pandemic vaccination during pregnancy. Objectives: We studied maternal A(H1N1)pdm09‐specific hemagglutination inhibition (HI)‐titer levels and waning in women with influenza‐like illness (ILI) in pregnancy compared to vaccinated women. Moreover, we studied the association between HI‐titers and self‐reported severity and duration of ILI. Methods: HI‐titers against the pandemic virus were measured in maternal blood samples obtained at birth, 3‐9 months after exposure, and linked with information about pregnancy, influenza and vaccination from national registries and a cohort questionnaire. Results: Among 1821 pregnant women included, 43.7% were unvaccinated and 19.3% of these had ILI. HI‐titers were low (geometric mean titer (GMT) 11.3) in the unvaccinated women with ILI. Higher HI‐titers (GMT 37.8) were measured in the vaccinated women. Estimated HI‐titer waning was similar for vaccinated women and women with ILI. Most ILI episodes were moderate and lasted 3‐5 days. Women with ILI reporting specific influenza symptoms such as fever or cough had higher HI‐titers than women without these symptoms. Women who reported being "very ill" or illness duration of >5 days had higher HI‐titers than women reporting less severe illness or illness of shorter duration, respectively. Conclusions: Antibody waning was similar in vaccinated women and women with ILI. More severe ILI or longer duration of illness was associated with higher HI‐titers. Most unvaccinated pregnant women with ILI had low HI‐titers, probably due to moderate illness and HI‐titer waning between exposure and sampling.